Burocratize not to corrupt: The impact of transnational actors on the anti-corruption measures of the national strategy to combat corruption and money laundering - Ricardo Staffen, Márcio (2020)
The research presented aims to analyze the impact of the actors transnational corporations in the alterations of the Brazilian anti-corruption state bureaucracy, through the guidelines established by the National Strategy for the Fight Against Corruption and Money Laundering of Capitals (National Strategy of Combat à Corrupção e à Lavagem de Ativos - ENCCLA). To this end, the text begins by addressing the global legal claim to prevent and combat corruption that spreads widely, conditioning and influencing, from scenarios transnationals, state mechanisms for standardization, regulation and action bureaucratic. In this sense, the evaluation of the actions of the National Strategy for Combat Corruption and Money Laundering (ENCCLA), in the period 2010-2020, points out the impact of transnational actors in the bureaucratization of national instruments anti-corruption, highlighting a mutation in the rationality of behaviors administrative, legislative and judicial mechanisms to prevent and combat corruption. Finally, the predominance of bureaucratic files, of orientation, stands out. transnational, in relation to democratic discourse and internal social perceptions, which they attribute to the bureaucracy the heart of acts of corruption. For the development of this research, the inductive method was used, operated by the techniques of operative concepts and Bibliographic research.